ELECTRONIC CONTROL OF SPEAKER PARAMETERS WITH ELECTROMECHANICAL FEEDBACK - Сулима, Николай Николаевич; Красовская, Наталья Леонидовна (Eastern-European Journal of Enterprise Technologies, 2010)
The ways of improvement of parameters of loudspeakers with electromechanical feedback were investigated. Some failings in existing variants of electromechanical feedback were defined. The method of elimination of the specified failings for loudspeakers is conceptually offered.